PEMBENTUKAN KATA PINJAMAN (GAIRAIGO) DALAM BAHASA JEPANG - Diah Soelistyowati (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2010)
This paper is trying to explain the formation of loanword fromEnglish to Japanese. It describes phonological change in gairaigo and identifies the morphological process that is the form and kind of gairaigo found in the use of gairaigo in automobile advertisements in Asahi Shinbun newspaper of January 2001-2002 edition. There are three conclusions that can be drawed in this research. First, the process of phonological change in gairaigo consists of three aspects: phoneme addition, phoneme deletion, and substitution. Second, the morphological process of gairaigo consists of form and kind. The forms of gairaigo are base form and derived form. Derived from in garaigo consists of compound word and abbreviation. Included in abbreviation are clipping, abbreviation, and acronym. Gairaigo forms found in data are nouns, verbs, and adjectives. Most gairaigo is noun. The verb can be formed by adding verb suru ‘doing’ preceded by English form. The adjective is followed by suffix -na, which is used in adjective loanwords. There is no gairaigo formation of affixation and thus the English loanword is adopted. Third, the overall process, both the phonological and the morphological, is a form of integration of foreign word into Japanese.Keywords: loanwords, compound word, clipping, abbreviation, acronym